Creating International Consensus on Combating Trafficking in Persons as a Human Rights Violation: U.S. Policy, the Role of the UN, and Global Responses and Challenges - Smith, Linda; Mattar, Mohamed (Tufts Archival Research Center, 2005)
Volume 28, Issue 1. Winter Former Congresswoman Linda Smith and Dr. Mohamed Mattar describe the scope of human trafficking, and describe the U.S. and global efforts necessary to restore human rights protections to traffickingï¿½s victims.